2021
DOI: 10.1021/acsphotonics.1c01339
|View full text |Cite
|
Sign up to set email alerts
|

Surface Recombinations in III-Nitride Micro-LEDs Probed by Photon-Correlation Cathodoluminescence

Abstract: III-nitride micro-LEDs are promising building blocks for the next generation of high performance micro-displays. To reach a high pixel density, it is desired to achieve micro-LEDs with lateral dimensions below 10 µm. With such pixel downscaling, sidewall effects are becoming important and an understanding of the impact of non-radiative surface recombinations is of vital importance. It is thus required to develop an adapted metric to evaluate the impact of these surface recombinations with a nanoscale spatial r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 35 publications
4
18
0
Order By: Relevance
“…Nevertheless, the CL-measured g (2) (Δ t ) of multiple defect centers shows strong photon bunching (Figure b) in contrast to PL-measured g (2) (Δ t ). ,, This bunching behavior originates from the synchronized emission from multiple centers excited by the same electron through the cascade decay. More recently, an experimental demonstration of the crossover between the bunching and antibunching regimes was provided by varying the electron-beam current in the CL study of color centers in diamond crystals, confirming the tunability of photon-correlation statistics in CL predicted by Meuret et al Based on a developed statistical model that determines the bunching strength g (2) (0) from the electron beam current, emitter decay lifetime, and electron excitation efficiency, the precise measurements of photon bunching permit retrieving the information about lifetime and excitation/emission efficiency of emitters with a high spatial resolution. For example, the nanoscale spatial distribution of excitation/emission efficiency for InGaN/GaN quantum wells is visualized by determining the CL-measured g (2) function in a spatially resolved manner as shown in Figure c. With advances in ultrafast microscopy, the photon correlation measurement with pulsed electron beams becomes another possible approach. , Furthermore, we note that a recent study presents a scheme to discriminate coherent and incoherent CL using photon correlation measurements, as well as quantifying their contributions to the detected signal, through measuring and fitting the specific bunching peak as the peak width is determined by the time scale of coherent and incoherent CL emission processes …”
Section: Review Of CL Nanoscopysupporting
confidence: 56%
“…Nevertheless, the CL-measured g (2) (Δ t ) of multiple defect centers shows strong photon bunching (Figure b) in contrast to PL-measured g (2) (Δ t ). ,, This bunching behavior originates from the synchronized emission from multiple centers excited by the same electron through the cascade decay. More recently, an experimental demonstration of the crossover between the bunching and antibunching regimes was provided by varying the electron-beam current in the CL study of color centers in diamond crystals, confirming the tunability of photon-correlation statistics in CL predicted by Meuret et al Based on a developed statistical model that determines the bunching strength g (2) (0) from the electron beam current, emitter decay lifetime, and electron excitation efficiency, the precise measurements of photon bunching permit retrieving the information about lifetime and excitation/emission efficiency of emitters with a high spatial resolution. For example, the nanoscale spatial distribution of excitation/emission efficiency for InGaN/GaN quantum wells is visualized by determining the CL-measured g (2) function in a spatially resolved manner as shown in Figure c. With advances in ultrafast microscopy, the photon correlation measurement with pulsed electron beams becomes another possible approach. , Furthermore, we note that a recent study presents a scheme to discriminate coherent and incoherent CL using photon correlation measurements, as well as quantifying their contributions to the detected signal, through measuring and fitting the specific bunching peak as the peak width is determined by the time scale of coherent and incoherent CL emission processes …”
Section: Review Of CL Nanoscopysupporting
confidence: 56%
“…In order to be able to link the CL efficiency drop at the centre of the large wires to a change of NRC density, we then used spatially resolved time-correlated cathodoluminescence (TC-CL) spectroscopy [34]. The measurement was achieved using an incident e-beam of 5 kV/10 pA.…”
Section: Resultsmentioning
confidence: 99%
“…This implies that TMAH considerably reduces sidewall recombination by eliminating the sidewall damage, resulting in a larger IQE after TMAH. Indeed, Finot et al [30] systemically investigating carrier lifetime characteristics cathodoluminescence, showed that the carrier lifetime near the sidewall could be enhanced with better sidewall conditions. This result is consistent with our TRPL and consequently the fact that better sidewall conditions improve the IQE of µLEDs.…”
Section: Influence Of the Tmah On Iqe And Non-radiative Recombinationmentioning
confidence: 99%